Nanoparticle‐microglial interaction in the ischemic brain is modulated by injury duration and treatment. Issue 3 (15th August 2020) - Joseph, Andrea; Liao, Rick; Zhang, Mengying; Helmbrecht, Hawley; McKenna, Michael; Filteau, Jeremy R.; Nance, Elizabeth
Abstract: Cerebral ischemia is a major cause of death in both neonates and adults, and currently has no cure. Nanotechnology represents one promising area of therapeutic development for cerebral ischemia due to the ability of nanoparticles to overcome biological barriers in the brain. ex vivo injury models have emerged as a high‐throughput alternative that can recapitulate disease processes and enable nanoscale probing of the brain microenvironment. In this study, we used oxygen–glucose deprivation (OGD) to model ischemic injury and studied nanoparticle interaction with microglia, resident immune cells in the brain that are of increasing interest for therapeutic delivery. By measuring cell death and glutathione production, we evaluated the effect of OGD exposure time and treatment with azithromycin (AZ) on slice health. We found a robust injury response with 0.5 hr of OGD exposure and effective treatment after immediate application of AZ. We observed an OGD‐induced shift in microglial morphology toward increased heterogeneity and circularity, and a decrease in microglial number, which was reversed after treatment. OGD enhanced diffusion of polystyrene‐poly(ethylene glycol) (PS‐PEG) nanoparticles, improving transport and ability to reach target cells. While microglial uptake of dendrimers or quantum dots (QDs) was not enhanced after injury, internalization of PS‐PEG was significantly increased. For PS‐PEG, AZ treatment restored microglial uptake to normal control levels. Our results suggest that different nanoparticle platforms should be carefully screened before application and upon doing so; disease‐mediated changes in the brain microenvironment can be leveraged by nanoscale drug delivery devices for enhanced cell interaction. Abstract :